Education, Knowledge, And Attitudes Impacting 1 House 1 Jumantik Implementation: A Study In The Kenten Laut Health Center's Working Area In 2019 - Ristawati Ristawati; Misnaniarti Misnaniarti; Mohammad Zulkarnain (Jurnal Indonesia Sosial Teknologi, 2023)
Dengue hemorrhagic fever is a major global problem because 2.5 to 3 billion people are at risk of developing this disease. Aedes Aegypti is the primary epidemic vector, an illness that usually affects urban areas but is starting to affect rural areas, estimated at around 50-100 million cases yearly. Dengue fever is transmitted through the bite of a female Aedes aegypti / Aedes albopictus, which carries the virus from other dengue fever sufferers. Therefore, dengue fever often causes death for sufferers. Given the danger of dengue fever, there needs to be a comprehensive eradication effort. The government has issued a Mosquito Nest Eradication policy (PSN 3M-Plus) to tackle dengue fever. This is the primary way considered effective, efficient, and economical to eradicate the vector of Dengue Dengue disease transmission, considering that drugs and vaccines that kill the dengue virus have not been found. Research method with a cross-sectional design, a sample of 100 households that meet the inclusion and exclusion criteria in the work area of the Kenten Laut Health Center. Data analysis with chi-square. The results of the study obtained There is a relationship between education (0.03), knowledge (0.041), and the implementation of the One House 1 Jumantik movement at the Kenten Laut Health Center. The puskesmas is advised to develop the One House 1 Jumantik movement so that the community is more responsible with their respective homes and can assist the Jumantik coordinator in implementing PJB.